Response of Blood Perfusion at ST 36 Acupoint after Drinking Cold Glucose or Saline Injection. (30th March 2017) - Wang, Guangjun; Jia, Shuyong; Li, Hongyan; Wang, Ze; Tian, Yuying; Zhang, Weibo
Abstract : Skin blood flux (SkBF) changes caused by drinking cold water are generally associated with vagal tone and osmotic factors in digestive system. According to acupuncture theory, change of SkBF at ST 36 might reflect the functional changes of digestive system. The aim of this study is to analyze the changes of SkBF after drinking 3°C 0.9% saline or 5% glucose injection by monitor blood flux at bilateral ST 36. The results indicated that, after drinking different cold water, the change ratio of SkBF at right side ST 36 has been different. Because all solutions have the same temperature (3°C) and both saline and glucose solution have the same osmolality, suggesting that the SkBF changes resulting from drinking cold water are not regulated just by the vagal tone and osmolality, there must have been other factors. These results have not been consistent with the frequency domain results of heart rate variability (HRV) analysis. Coherence analysis of blood flux signals at bilateral ST 36 indicated that there have been different coherence-frequency curves among different groups in special frequency bands, which suggested that coherence analysis might provide a potential tool to evaluate different status.